2019
DOI: 10.3389/fsurg.2019.00045
|View full text |Cite
|
Sign up to set email alerts
|

Delta-Aminolevulinic Acid-Mediated Photodiagnoses in Surgical Oncology: A Historical Review of Clinical Trials

Abstract: Fluorescence imaging is an emerging clinical technique for real-time intraoperative visualization of tumors and their boundaries. Though multiple fluorescent contrast agents are available in the basic sciences, few fluorescence agents are available for clinical use. Of the clinical fluorophores, delta aminolevulinic acid (5ALA) is unique for generating visible wavelength tumor-specific fluorescence. In 2017, 5ALA was FDA-approved for glioma surgery in the United States. Additionally, clinical studies suggest t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 87 publications
(115 reference statements)
0
15
0
Order By: Relevance
“…In Fig. 10, the external irradiation optical source power (laser module) of a conventional surgical microscope was 55-160 mW/cm 2 [4], [15], [18], [25]- [29], and the working distance was 15-30 cm [4,15,18,23,25,29]. However, the external irradiation optical intensity will have losses of approximately 58 % when the working distance is above the minimum of 200 mm [30].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In Fig. 10, the external irradiation optical source power (laser module) of a conventional surgical microscope was 55-160 mW/cm 2 [4], [15], [18], [25]- [29], and the working distance was 15-30 cm [4,15,18,23,25,29]. However, the external irradiation optical intensity will have losses of approximately 58 % when the working distance is above the minimum of 200 mm [30].…”
Section: Discussionmentioning
confidence: 99%
“…4 shows the fabrication of a pen-type probe that was created via the 3 D printing technique. The overall size and weight of the pen-type probe were 17 mm × 2.5 mm and 32 g (± 2 g), respectively; the weight of the conventional surgical microscope is 6.0 kg [20]- [23]. Thus, the pentype probe is lighter than the conventional surgical microscope.…”
Section: Design Of the Pen-type Probementioning
confidence: 98%
See 2 more Smart Citations
“…82 No studies utilizing any modied third-generation porphyrins for the PDD of CRC were found. 83 Chlorins. A study by Gavrina et al (2018), explored the PDT efficacy of Chlorin e6 (Ce6) conjugated to polyvinyl alcohol (PVA) nanoparticles in CRC CT26 xenogra models.…”
Section: Photosensitizers For Pdd and Pdt Colorectal Cancer Applicationsmentioning
confidence: 99%